Pengaruh Profitabilitas Dan Leverage Terhadap Nilai Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2022 - Jeri Kurnia; Muhammad Rivandi (Jurnal Riset Ekonomi dan Akuntansi, 2024)
Company value is something important and is the company's main object to continue to increase its company value as a going concern for the company's survival in the future. This research aims to determine the effect of profitability and leverage on company value. The research population of banking sector companies, the research sample was 24 companies selected using a purposive sampling technique with an observation period of 2019-2022. The data analysis method used in this research is a panel data regression model. Based on the test results, profitability has no effect on company value and leverage has a significant positive effect on company value.